Anti-tumor effect of Liqi, a traditional Chinese medicine prescription, in tumor bearing mice - Jiang Yi-Min; Ye Jia; Ji Deng-Bo; Qian Bo-Wen (BMC, 2009)
Abstract Background Liqi, an herbal preparation used in traditional Chinese medicine, has been used to treat cancer in China for centuries. We investigated the anti-tumor effects of liqi and their mechanisms in mice that had been xenografted with tumors. Methods Sarcoma 180 tumor, Lewis lung carcinoma, and SGC-7901 cells were implanted in BALB/c mice, C57BL/6 mice, and BALB/c nude mice, respectively. Liqi was administered to subgroups of these mice. The tumor weight and size were measured. Cell cycle analysis and T lymphocyte subsets were determined by flow cytometry. The activity of NK cells and TNF was tested using cytotoxicity assay on YAC-1 cells and L929 cells, respectively, and the activity of IL-2 was tested with an IL-2-dependent CTLL-2 cell proliferation assay. Platelet aggregation was monitored by measuring electric impedance, and the levels of thromboxane A2 (TXA2) and prostacyclin (PGI2) in blood were measured by 125I-TXB2 and 125I-Keto-PGF1α radioimmunoassay. Results The results showed that liqi inhibited tumor growth in tumor-implanted mice and arrested the cell proliferation in the G0/G1 phase and reduced the portion of cells in S and G2/M phase for SGC-7901 cells. Liqi increased the activity of NK cells and TNF-α, stimulated IL-2 production and activity, and regulated T lymphocyte subpopulations. Liqi inhibited the Lewis lung carcinoma metastasis by inhibiting platelet aggregation and normalizing the balance between TXA2 and PGI2. Conclusion All these findings demonstrated that liqi has an anti-tumor effect in vivo. The mechanism may be related to immune regulation and anticoagulation effects.